Anesthetic consideration in dystrophic epidermolysis bullosa - A S Narejo; M U Khan; W M Alotaibi; M M Khan (Saudi Journal of Anaesthesia, 2016)
Epidermolysis bullosa is a group of inherited rare skin disease, characterized by bullae formation in the skin or mucous membranes. The fundamental abnormality is collagen degeneration leads to splitting of various epidermal layers. Dystrophic epidermolysis bullosa (DEB) is one of the major forms of epidermolysis bullosa. These patients often admitted to the hospital for corrective surgeries, change of dressing, contracture release, and skin grafting. Anesthetic management of these cases is always a challenge. We are reporting a case of 5-year-old boy diagnosed as a case of DEB scheduled for upper lip contracture release, skin grafting and debridement of nonhealing scars under anesthesia. In this case, we have focused mainly on the anesthetic management, preparation of the monitoring, transportation, difficulties in establishing the venous accesses, and airway management.